CRISPR-Cas9: An Evolutionary Technique for the Treatment of Breast and Cervical Carcinoma - Shah, Syed SIb Tul Hassan (Asian Pacific Journal of Environment and Cancer, 2024)
CRISPR/Cas9 has transformed genome editing methods in several scientific domains, including the study of human cancer. Globally, breast cancer (BC) affects women more than any other kind of cancer and triple-negative breast cancer (TNBC) has the greatest fatality rate. The diagnosis and treatment of breast cancer have come a long way, yet many patients still experience metastases or relapses. One of the potential techniques for correcting faulty genes and curing different cancers is gene therapy. Certain mutations associated with cancer onset and development might be repaired in model organisms as a first step toward translational applications using the CRISPR/Cas9 technology. The CRISPR/Cas9 system, which consists of a single readily modified guide RNA (sgRNA) sequence coupled to a Cas9 nuclease, has transformed genome editing owing to its simplicity and effectiveness when compared to previous methods. CRISPR/Cas9 allows for the knockdown of over-expressed genes, the reversal of mutations in defected genes, and the remodeling of the regulatory environment to inhibit BC proliferation. CRISPR/Cas9-based treatment mixed with traditional chemotherapy has proven to be beneficial in combating drug resistance and tumor inhibition difficulties. The CRISPR cas9 system may edit many genes at the same time by generating numerous sgRNAs that target different genomic regions, considerably increasing its therapeutic potential and making it a unique technique for treating cervical lesions. This review focuses on the therapeutic applications of CRISPR/Cas9 in the treatment of cervical cancer and breast cancer.